Pemberdayaan Ekonomi Pasien Thalassemia Melalui Kegiatan Bisnis Online di Banyumas - Lantip Rujito; Diyah Woro Dwi Lestari; Qodri Santosa; Ariadne Tiara Hapsari (Jurnal Pengabdian Pada Masyarakat, 2017)
ECONOMIC EMPOWERING OF THALASSEMIA PATIENTS THROUGH ONLINE ENTREPREUNERS ACTIVITIES IN BANYUMAS. Thalassemia in Banyumas is a part of portrait of Indonesia’s problems. Todays, there is not yet any national thalassemia countermeasures program so that thalassemia prevalence is getting increased year by year. Increasing life expectancy of thalassemia patients brings economical problem consequence. Social stigma and businessmen support Thalassemia patients to be powered economically in their productive age. Entrepreneurship autonomy becomes an alternative to overcome it. Online entrepreneurs has flexibility, creative space, global range and unlimited time that support it to be an optional solution for preparing thalassemia patients welcoming productive age.